Revisions of international consensus Fukuoka guidelines for the management of IPMN of the pancreas - Tanaka, Masao; Fernández-del Castillo, Carlos; Kamisawa, Terumi; Jang, Jin Young; Levy, Philippe; Ohtsuka, Takao; Salvia, Roberto; Shimizu, Yasuhiro; Tada, Minoru; Wolfgang, Christopher L. (Pancreatology : official journal of the International Association of Pancreatology (IAP) ... [et al.], 2017)
The management of intraductal papillary mucinous neoplasm (IPMN) continues to evolve. In particular, the indications for resection of branch duct IPMN have changed from early resection to more deliberate observation as proposed by the international consensus guidelines of 2006 and 2012. Another guideline proposed by the American Gastroenterological Association in 2015 restricted indications for surgery more stringently and recommended physicians to stop surveillance if no significant change had occurred in a pancreatic cyst after five years of surveillance, or if a patient underwent resection and a non-malignant IPMN was found. Whether or not it is safe to do so, as well as the method and interval of surveillance, has generated substantial debate. Based on a consensus symposium held during the meeting of the International Association of Pancreatology in Sendai, Japan, in 2016, the working group has revised the guidelines regarding prediction of invasive carcinoma and high-grade dysplasia, surveillance, and postoperative follow-up of IPMN. As the working group did not recognize the need for major revisions of the guidelines, we made only minor revisions and added most recent articles where appropriate. The present guidelines include updated information and recommendations based on our current understanding, and highlight issues that remain controversial or where further research is required.